The risk analysis by failure mode and effect analysis (FMEA) and fuzzy-FMEA of supercritical water gasification system used in the sewage sludge treatment - Adar, Elanur; Ince, Mahir; Karatop, Buket; Bilgili, Mehmet Sinan (ELSEVIER SCI LTD, 2017)
Supercritical water gasification (SCWG) system is a hydrothermal conversion process used for the treatment of wastes with organic and toxic content and it is an especially promising technology for biomass with high water content such as sewage sludge. The interest in this technology is on a paramount increase because of both economic and environmental reasons. However, this system is marked by certain problems even though it has significant advantages. The aim of this study is to determine the problems that occur during the commissioning and operation of a continuously operated, laboratory-scale supercritical water gasification system and to identify their reasons and effects. For this purpose, cause-and-effect diagram, classical failure mode and effect analysis and fuzzy failure mode and effects analysis were carried out. As a result of the analyses performed, it has been concluded that the most important problems are plugging, corrosion, reactor design and incompatible material selection. As for the most important risks that occur in SCWG, they include explosion, injury, odor and noise. It has been seen that conducting a risk analysis of the SCWG system is important for job safety and sound operation. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Supercritical water gasification; Risk analysis; Cause-and-effect diagram; FMEA; Fuzzy logic; TRANSPIRING WALL REACTOR; TEMPERATURE; PARAMETERS; Engineering